From Homo’poly to Openup! lessons learned on LGB in education in schools across Europe - Geunis, Lotte; Holz, Oliver (Revija za elementarno izobraževanje, 2020)
This paper captures the lessons learned from Homo’poly, an ERASMUS+ project on awareness and understanding of homosexuality in schools. Homo’poly was implemented between 2016 and 2019 in eight European countries: Belgium, Germany, the Netherlands, Poland, Spain, Turkey, Hungary and the United Kingdom. Throughout the project, partner institutions noted that homophobia, a lack of wider community engagement and (notably in Central and Eastern Eruope) limited political support proved to be significant stumbling blocks. The authors build on a survey of partner institutions to further explore these challenges and set out proposed directions for future activities and research.
Keywords: Education, LGBT; Europe; ERASMUS; homophobia